OTORITAS PRESIDEN DALAM MENETAPKAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG (Tinjauan Fiqh Siyasah Dusturiyyah dan Hukum Positif) - Ariska Ade Putra; Nailur Rahmi (Jurnal Integrasi Ilmu Syariah (Jisrah), 2021)
The problem in this research is how the president's authority in determining government regulations to replace laws is reviewed from the fiqh siyasah, a form of urgency that forces the establishment of government regulations to substitute laws according to positive law. The purpose of this discussion is to find out how the president's authority in issuing government regulations in lieu of laws is reviewed from the fiqh siyasah, a form of urgency that forces the establishment of government regulations in lieu of laws according to positive law.